2013
DOI: 10.1111/febs.12225
|View full text |Cite
|
Sign up to set email alerts
|

Signal transducer and activator of transcription 6 directly regulates human ORMDL3 expression

Abstract: Orosomucoid-like 3 (ORMDL3) has been associated with asthma and a series of autoimmune disorders, and is involved in endoplasmic reticulummediated inflammatory responses. However, its clinical significance and the molecular mechanism underlying its expression are still largely unclear. To elucidate the mechanisms of human ORMDL3 transcriptional regulation, we cloned a 1.5 kb genomic DNA fragment containing the putative promoter region and evaluated its transcriptional activity in a luciferase reporter system b… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
19
0

Year Published

2014
2014
2017
2017

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 26 publications
(21 citation statements)
references
References 59 publications
(80 reference statements)
2
19
0
Order By: Relevance
“…Firstly, in vitro study of the ORMDL3 promoter revealed that Est-1, p300, and CREB are regulators of ORMDL3 expression and that the levels of these regulators correlated with expression of ORMDL3 in recurrent wheeze patients (43). Later, STAT6 was shown to be a direct regulator of ORMDL3 expression (44), confirming previous findings that both ORMDL3 and STAT6 are associated with asthma (45). Furthermore, the role of chromatin in ORMDL3 expression was evaluated.…”
Section: Association Of Ormdl3 With Asthma and Other Pathologiessupporting
confidence: 75%
See 3 more Smart Citations
“…Firstly, in vitro study of the ORMDL3 promoter revealed that Est-1, p300, and CREB are regulators of ORMDL3 expression and that the levels of these regulators correlated with expression of ORMDL3 in recurrent wheeze patients (43). Later, STAT6 was shown to be a direct regulator of ORMDL3 expression (44), confirming previous findings that both ORMDL3 and STAT6 are associated with asthma (45). Furthermore, the role of chromatin in ORMDL3 expression was evaluated.…”
Section: Association Of Ormdl3 With Asthma and Other Pathologiessupporting
confidence: 75%
“…A recent study with IL-13 knockout mice described the dependence of ORMDL3 overexpression on IL-13 (67). It has also been shown that IL-4 and IL-13 induction of ORMDL3 expression is STAT6 dependent (44). Very similar regulation of ORMDL3 expression was observed in studies of fatty acid-binding protein 4 (FABP4), which is known to regulate allergic airway inflammation and provides a link between the fatty acid metabolism and asthma phenotype (99).…”
Section: The Role Of Ormdls In Immune Response Regulationmentioning
confidence: 76%
See 2 more Smart Citations
“…To further validate the co-occupancy of NOL1 and hTERT in the cyclin D1 promoter, we performed a ChIP-re-ChIP assay (Qiu et al, 2013). HeLa S3 cells expressing Flag-hTERT and NOL1-V5 were subjected to ChIP with anti-Flag antibody, followed by re-ChIP using anti-V5 antibody.…”
Section: Nol1 Activates Transcription Of the Cyclin D1 Genementioning
confidence: 99%